Hegemoni Barat dalam Dunia Akademik: Tinjauan Filosofis atas Implikasi dan Jalan Menuju Dekolonisasi Pengetahuan - Lidya Lestari; Hasinah Jindan; Najwa Najwa (CV. Eureka Artha Nusantara, 2026)
This article aims to philosophically analyze the institutional hegemony of the Western model in the academic world and its implications for global epistemic justice. Through a critical literature review, this study identifies how Western epistemological foundations—rooted in rationalism, objectivity, and universalism—have shaped the structure of modern higher education institutions, particularly through colonialism, positivism, and postcolonial globalization. This model has become institutionalized in curricula, research methodologies, publication standards, and academic evaluation mechanisms, which in turn produce phenomena such as epistemicide and intellectual homogenization. Using a decolonial theoretical framework, the article examines various forms of epistemic violence and universalistic bias that position non-Western knowledge as inferior. The findings affirm the need for pluriversality as an alternative paradigm to build more inclusive and equitable academic institutions. The article proposes decolonization pathways through curriculum reform, decolonial pedagogy, the opening of inter-epistemic dialogical spaces, and critical engagement with biased international standards. This study contributes to efforts toward epistemological and institutional reconstruction, particularly within a global academic context still overshadowed by the legacy of colonialism.